Extractivism and unconventional hydrocarbons: the advance of fracking in the protected natural area of Auca Mahuida (Neuquén, Argentina) - Acacio, Juan Antonio (2021)
This article aims to problematize the entry of the unconventional hydrocarbon activity that is carried out by means of the fracking technique, or hydrofracture, to the protected natural area of Auca Mahuida, in the province of Neuquén, Argentina. In order to account for the advance of extractivism in these peculiar territories, we take the case of Auca Mahuida’s analysis to investigate, with a strong descriptive and chronological component, in the way in which the state technical sectors in charge of the administration of these areas they problematized the entry of the Total Austral company into protected territory. We focus on the diagnoses and the links that they forged with the movement that sought to resist unconventional activity at the provincial level that began to develop strongly in 2013. In this key, we also realize the jump in scale of the conflict by getting involved the organization Friends of the Earth France, which carried out a reading in terms of north/south ecological debt regarding the activities of the French company.